2017
DOI: 10.1016/j.jfca.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of lipid content and fatty acid composition in muscle, liver and gonads of Seriola fasciata Bloch 1793 based on gender and maturation stage

Abstract: The fat content and fatty acid profile of commercially important Seriola fasciata (Lesser amberjack) was determined in samples of muscle, liver and gonads of both genders at pre-spawning and spawning stage. Results indicated that edible muscle of pre-spawning fish had high fat content (>8%), lowering to medium fat (4-8%) content during spawning stage. Livers and gonads presented more constant and relatively high lipid contents. Saturated fatty acids constituted the majority of the fatty acids, followed by mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
(33 reference statements)
2
17
0
Order By: Relevance
“…Overall, females at prespawning stage presented higher lipid content in all sampled tissues, with a marked increase in dorsal muscle. Dorsal muscle lipid content was higher in our samples (24.04%) when compared to the results found in the muscle of S. fasciata at the same maturation stage (Nogueira et al, 2016) and of S. dumerilli (Haouas, Zayene, Guerbej, Hammami, & Achour, 2010;Rodríguez-Barreto et al, 2012), but similar to those found by Rodríguez-Barreto et al (2014) in indoor cultivated S. dumerilli. Such differences highlight the need of knowing fish nutritional value, especially when fish are not easy to distinguish, as is the case between Almaco jack adults and greater amberjack juveniles.…”
Section: Total Lipidsupporting
confidence: 77%
See 3 more Smart Citations
“…Overall, females at prespawning stage presented higher lipid content in all sampled tissues, with a marked increase in dorsal muscle. Dorsal muscle lipid content was higher in our samples (24.04%) when compared to the results found in the muscle of S. fasciata at the same maturation stage (Nogueira et al, 2016) and of S. dumerilli (Haouas, Zayene, Guerbej, Hammami, & Achour, 2010;Rodríguez-Barreto et al, 2012), but similar to those found by Rodríguez-Barreto et al (2014) in indoor cultivated S. dumerilli. Such differences highlight the need of knowing fish nutritional value, especially when fish are not easy to distinguish, as is the case between Almaco jack adults and greater amberjack juveniles.…”
Section: Total Lipidsupporting
confidence: 77%
“…The total fatty acids (mg/100g sample) were higher in the liver samples from both maturation stages, followed by dorsal muscle of pre-spawning females. Comparison with S. fasciata at the same maturation stage and captured in the same region (Nogueira et al, 2016), indicates that Almaco jack muscle samples are richer (9.737, 19.174 and 8.205 g/100g) than S. fasciata (6.514, 13.857 and 7.959 g/100g) in all sampled tissues (muscle, liver and gonad, respectively).…”
Section: Fatty Acid Profilesmentioning
confidence: 91%
See 2 more Smart Citations
“…Other reported sex‐based differences in lipid composition at the time of spawning include n ‐3/ n ‐6 ratios of liver lipids between male and female lesser amberjack ( Seriola fasciata ; Nogueira, Fernandes, Fernandes, & Cordeiro, 2017). Recent research has demonstrated that some fishes can provision ova directly from the diet, as well as from somatic sources; coho salmon ( Oncorhynchus kisutch ) were shown to preferentially deposit ARA and DHA from their diet into developing ovaries (Johnson, Kroeger, Reichert, Carter, & Rust, 2017).…”
Section: Discussionmentioning
confidence: 99%